Mammaglobin B expression in human endometrial cancer. Issue 5 (1st August 2008) - Tassi, R. A.; Bignotti, E.; Falchetti, M.; Calza, S.; Ravaggi, A.; Rossi, E.; Martinelli, F.; Bandiera, E.; Pecorelli, S.; Santin, A. D.
Abstract : Mammaglobin B (MGB-2) is an uteroglobin gene family member recently found highly differentially expressed in ovarian cancer by gene expression profiling. To evaluate its potential as a novel endometrial cancer biomarker, in this study we quantified and compared MGB-2 expression at messenger RNA and protein levels in endometrial tumors (endometrioid endometrial cancer [EEC]) with different grades of differentiation. MGB-2 expression was evaluated by real-time polymerase chain reaction (PCR) and immunohistochemistry (IHC) in fresh frozen biopsies and paraffin-embedded tissues derived from a total of 70 patients including 50 primary EEC and 20 normal endometria (NECs). High levels of MGB-2 gene expression were detected in 10 of 11 EEC G1 cases (91%), 16 of 17 EEC G2 cases (94%), and 6 of 22 EEC G3 cases (27%) by real-time PCR. In contrast, normal endometrial cells expressed low to negligible levels of MGB-2 by real-time PCR ( P = 0.002 EEC vs NEC). Well- and moderately differentiated EECs overexpressed MGB-2 gene at significant higher levels when compared to NECs ( P < 0.01). Pairwise differences between both G2 and G1 vs G3 cases for MGB-2 relative gene expression values were also statistically significant (G2 vs G3 P < 0.001, G1 vs G3 P = 0.016). MGB-2 protein expression was detected in 31 (86%) of 36 EEC and 0 of 5 atrophic NEC controls, while seven of eight (88%) of the proliferative/secretory/hyperplastic NECs focally expressed MGB-2 by IHC. MGB-2 is highly expressed in EEC, particularly in well- and moderately differentiated tumors, and may represent a novel molecular marker for EEC.